The inhibitory effect of minocycline on radiation-induced neuronal apoptosis via AMPKα1 signaling-mediated autophagy. Issue 1 (December 2017) - Zhang, Liyuan; Huang, Ping; Chen, Hui; Tan, Wen; Lu, Jiawei; Liu, Wei; Wang, Jingdong; Zhang, Shuyu; Zhu, Wei; Cao, Jianping; Tian, Ye; Yang, Hongying
Abstract Due to an increasing concern about radiation-induced cognitive deficits for brain tumor patients receiving radiation therapy, developing and evaluating countermeasures has become inevitable. Our previous study has found that minocycline, a clinical available antibiotics that can easily cross the blood brain barrier, mitigates radiation-induced long-term memory loss in rats, accompanied by decreased hippocampal neuron apoptosis. Thus, in the present study, we report an unknown mechanism underlying the neuroprotective effect of minocycline. We demonstrated that minocycline prevented primary neurons from radiation-induced apoptosis and promoted radiation-induced autophagyin vitro . Moreover, using an immortalized mouse hippocampal neuronal cell line, HT22 cells, we found that the protective effect of minocycline on irradiated HT22 cells was not related to DNA damage repair since minocycline did not facilitate DNA DSB repair in irradiated HT22 cells. Further investigation showed that minocycline significantly enhanced X-irradiation-induced AMPKα1 activation and autophagy, thus resulting in decreased apoptosis. Additionally, although the antioxidant potential of minocycline might contribute to its apoptosis-inhibitory effect, it was not involved in its enhancive effect on radiation-induced AMPKα1-mediated autophagy. Taken together, we have revealed a novel mechanism for the protective effect of minocycline on irradiated neurons, e.g. minocycline protects neurons from radiation-induced apoptosis via enhancing radiation-induced AMPKα1-mediated autophagy.